2009
DOI: 10.1111/j.1574-6941.2008.00634.x
|View full text |Cite
|
Sign up to set email alerts
|

Surveillance of vibriophages reveals their role as biomonitoring agents in Kolkata

Abstract: Cholera is a public health threat in all developing countries. Kolkata, a city in eastern India, is an endemic zone for cholera. During the course of a comprehensive investigation on the distribution of phages of Vibrio cholerae O1 and O139 in freshwater bodies in Kolkata, we were able to isolate the phages of V. cholerae O1 and O139. Vibrio cholerae O1 phages were found at all the sites and exhibited a distinct seasonal cycle, with a primary peak (13.6-17.2 PFU mL(-1)) during monsoon (June to August) in both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…However, there was only a weak correlation between temperature and TBC (R = 0.43, P = 0.019, N = 29 for DH and R = 0.48, P = 0.002, N = 32 for HB). Contrasting with this, CVC and temperature correlated highly significant at HB (R = 0.733, P = b0.001, N = 32) which is supported by earlier findings reporting an increase of CVC with temperature in natural waters (e.g., Nair et al, 1988; Das et al, 2009;Neogi et al, 2011). However, in our case within the same estuary, but at higher salinities, CVC and temperature show a much lower correlation (R = 0.332, P = 0.078, N = 29) at DH, which stresses the importance of further environmental parameters.…”
Section: Effect Of Physico-chemical Variations On Bacterial Abundancesupporting
confidence: 82%
“…However, there was only a weak correlation between temperature and TBC (R = 0.43, P = 0.019, N = 29 for DH and R = 0.48, P = 0.002, N = 32 for HB). Contrasting with this, CVC and temperature correlated highly significant at HB (R = 0.733, P = b0.001, N = 32) which is supported by earlier findings reporting an increase of CVC with temperature in natural waters (e.g., Nair et al, 1988; Das et al, 2009;Neogi et al, 2011). However, in our case within the same estuary, but at higher salinities, CVC and temperature show a much lower correlation (R = 0.332, P = 0.078, N = 29) at DH, which stresses the importance of further environmental parameters.…”
Section: Effect Of Physico-chemical Variations On Bacterial Abundancesupporting
confidence: 82%
“…Detection and quantification of V. cholerae, especially of serogroup O1/O139 strains in environmental samples, are still difficult tasks, and no international standard is available. Currently accepted cultivation-based methods take at least 48 h to obtain a final result (5) and severely underestimate the presence of O1/O139 serogroups, due to the fact that these strains predominantly enter a viable but nonculturable (VBNC) state once released from the human intestine into the environment (6,7). Alternatively, fluorescence in situ hybridization (FISH) and the direct fluorescent-antibody assay (DFA) are direct cell-based detection methods that include VBNC bacteria.…”
mentioning
confidence: 99%
“…[ 15 ] We have previously reported that phages act as a biomonitoring agent in the environment, provides important insights in V. cholerae surveillance. [ 4 ] Predation on pathogenic V. cholerae may be an important factor influencing the epidemic cycle on short-time scales and may act to modify the duration and severity of cholera outbreaks. [ 16 ]…”
Section: Discussionmentioning
confidence: 99%
“…[ 3 ] Earlier studies showed a correlation between V. cholerae O1 and its phages (vibriophages) in different environmental water samples of natural water bodies. [ 4 5 ] Because of its stability and less sensitivity vibriophages appear to be better indicators and suggested to be used as a biomonitoring agent in different aquatic ecosystems. Although V. cholerae is a human pathogen, they constitute part of the normal aquatic flora also in water environments,[ 6 ] and water is established a transmission vehicle.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation